2021
DOI: 10.3390/vetsci8120332
|View full text |Cite
|
Sign up to set email alerts
|

Pet Ownership and Quality of Life: A Systematic Review of the Literature

Abstract: Pet ownership is the most common form of human–animal interaction, and anecdotally, pet ownership can lead to improved physical and mental health for owners. However, scant research is available validating these claims. This study aimed to review the recent peer reviewed literature to better describe the body of knowledge surrounding the relationship between pet ownership and mental health. A literature search was conducted in May 2020 using two databases to identify articles that met inclusion/exclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 77 publications
7
48
0
Order By: Relevance
“…Beetz, 2017 ). These findings coincide with research in adult populations that find stress is reduced through AAI (Friedmann & Son, 2009 ; Pendry et al, 2020 ; Scoresby et al, 2021 ). Generally, AAI research with dogs demonstrates the positive impact they can have on young learners’ academic performance (Lane & Zavada, 2013 ), emotional regulation, and social skills (Beetz et al, 2012 ).…”
Section: Literature Reviewsupporting
confidence: 88%
“…Beetz, 2017 ). These findings coincide with research in adult populations that find stress is reduced through AAI (Friedmann & Son, 2009 ; Pendry et al, 2020 ; Scoresby et al, 2021 ). Generally, AAI research with dogs demonstrates the positive impact they can have on young learners’ academic performance (Lane & Zavada, 2013 ), emotional regulation, and social skills (Beetz et al, 2012 ).…”
Section: Literature Reviewsupporting
confidence: 88%
“…In particular, rabbits are increasingly common in the home environment in some countries such as the United Kingdom [2]. Pets provide great social benefits to owners such as decreasing feelings of loneliness and anxiety and increasing opportunities for socialization [3]. Moreover, dogs, cats, horses, rabbits, and hamsters are frequently used in Animal-assisted Therapy (AAT).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these benefits, human-animal interactions are associated with risks of health problems, including allergies, asthma, animal bites, and scratches [4]. In addition, pets are not always able to provide a positive effect in case of mental illness or untreated stress in people [3]. Companion animals can also transmit potential pathogens to humans.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that owning a dog leads to a 24% reduction in the risk of all‐cause mortality at all ages, 16 a 31% reduction in the risk of cardiovascular disease, 16–18 greater physical activity, 19 and greater ability to embrace a healthy lifestyle 20,21 . Just as in younger individuals, older dog owners benefit from the effects of walking a dog 22–27 . The benefit of dog ownership might also be combined with a perceived good physical health and may facilitates the development of new social relationships Recent reviews suggest that dog ownership could benefit children's and adult's mental health 24–26 …”
Section: Introductionmentioning
confidence: 99%